Palivizumab e virus respiratorio sinciziale: una panoramica - Manzoni, Paolo (Farmeconomia. Health Economics and Therapeutic Pathways, 2011)
Respiratory Syncytial Virus (RSV) is a very frequent cause of respiratory infections in the first two years of life. Symptoms often are mild to moderate, but in some high-risk categories of infants, particularly prematures and children with bronchopulmonary dysplasia or congenital heart disease, RSV can cause severe lower respiratory tract infections with need of hospitalisation, and, sometimes, even death. No effective treatment is available, and specific vaccines, despite several attempts during the last decades, do not exist. Palivizumab is a humanised monoclonal antibody targeting specific viral mechanisms controlling infection. If administered intramuscularly monthly during the RSV season as prophylaxis to high risk patients < 2 years of age, this antibody effectively reduces hospitalisation rates and severity of RSV infection. Based on the data from the two main phase III trials conducted so far, palivizumab prophylaxis results in 45% to 55% reduction of hospitalisation rate, with a very satisfactory profile of tolerability as most commonly reported adverse events where transient and mild irritability, diarrhoea or fever.